Water hyacinth canopy and pan evaporation - RATHORE, L. S.; MASKE, S. J.; SHAHA, S. K. (MAUSAM, 1984)
Water losses from open pan evaporimeter covered with water hyacinth, an aquatic weed, and from an open pan evaporimeter were compared to find out tentatively, the quantitative effect of water hyacinth canopy on evaporation. It was found that water hyacinth canopy doubles the water losses due to its higher transpiration rate. A quantitative description of water hyacinth canopy and its use in computation of evaporation from large water bodies is outlined.